2021
DOI: 10.1002/dvdy.357
|View full text |Cite
|
Sign up to set email alerts
|

The use of transgenics in the laboratory axolotl

Abstract: The ability to generate transgenic animals sparked a wave of research committed to implementing such technology in a wide variety of model organisms.Building a solid base of ubiquitous and tissue-specific reporter lines has set the stage for later interrogations of individual cells or genetic elements. Compared to other widely used model organisms such as mice, zebrafish and fruit flies, there are only a few transgenic lines available in the laboratory axolotl (Ambystoma mexicanum), although their number is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Reproductive characteristics of animal laboratory models used for transgenesis/genome editing experiments. References: (a) (Butt et al, 1992), (b) (Akazawa et al, 2021), (c) (Dominguez & Edwards, 2010), (d) (Shankland et al, 1992), (e) (Iyer et al, 2019), (f) (Williams & Jékely, 2016), (g) (A. H. L. Fischer et al, 2010), (h) (Seaver, 2016), (i) (Ebert, 2005), (j) (Yamaguchi & Yoshida, 2018), (k) (Schröder et al, 2008), (l) (Howe, 1962), (m) (Lawrence et al, 2012), (n) (Wittbrodt et al, 2002), (o) (Jeffery, 2020), (p) (Blackburn & Miller, 2019), (q) (Beck & Slack, 2001), (r) (Wolf & Hedrick, 1971), (s) (Tilley et al, 2022), (t) (Phifer-Rixey & Nachman, 2015), (u) (Weber & Olsson, 2008), (v) (Darling et al, 2005), (w) (Kaliszewicz, 2011), (x) (Massaro & Rocha, 2008), (y) (Frank et al, 2001), (z) (Lechable et al, 2020), (aa) (Iglesias et al, 2004), (bb) (Meneely et al, 2019) Table 2 provides an overview of current metazoan models that have been acclimated in laboratory settings for experiments involving genetics and reverse genetics. This list includes a mix of models that have been developed for a long time, some for more than a century, with well-established protocols and numerous publications utilizing these techniques (such as the house mouse, fruit fly, and Caenorhabditis elegans), as well as several other models where efforts to develop genetic approaches are still in their early stages.…”
Section: Comparison With Other Metazoan Modelsmentioning
confidence: 99%
“…Reproductive characteristics of animal laboratory models used for transgenesis/genome editing experiments. References: (a) (Butt et al, 1992), (b) (Akazawa et al, 2021), (c) (Dominguez & Edwards, 2010), (d) (Shankland et al, 1992), (e) (Iyer et al, 2019), (f) (Williams & Jékely, 2016), (g) (A. H. L. Fischer et al, 2010), (h) (Seaver, 2016), (i) (Ebert, 2005), (j) (Yamaguchi & Yoshida, 2018), (k) (Schröder et al, 2008), (l) (Howe, 1962), (m) (Lawrence et al, 2012), (n) (Wittbrodt et al, 2002), (o) (Jeffery, 2020), (p) (Blackburn & Miller, 2019), (q) (Beck & Slack, 2001), (r) (Wolf & Hedrick, 1971), (s) (Tilley et al, 2022), (t) (Phifer-Rixey & Nachman, 2015), (u) (Weber & Olsson, 2008), (v) (Darling et al, 2005), (w) (Kaliszewicz, 2011), (x) (Massaro & Rocha, 2008), (y) (Frank et al, 2001), (z) (Lechable et al, 2020), (aa) (Iglesias et al, 2004), (bb) (Meneely et al, 2019) Table 2 provides an overview of current metazoan models that have been acclimated in laboratory settings for experiments involving genetics and reverse genetics. This list includes a mix of models that have been developed for a long time, some for more than a century, with well-established protocols and numerous publications utilizing these techniques (such as the house mouse, fruit fly, and Caenorhabditis elegans), as well as several other models where efforts to develop genetic approaches are still in their early stages.…”
Section: Comparison With Other Metazoan Modelsmentioning
confidence: 99%
“…Compared to zebrafish, axolotls are larger(up to 30 cm in length), allowing serial blood collection, more complicated surgical operations, and the use of imaging techniques such as magnetic resonance imaging, echocardiography, and positron emission tomography [80]. Zebrafish are more well-studied genetically, but there are developed genomic databases of the axolotl, and several transgenetic axolotl models have been applied [84][85][86][87][88]. How the axolotl can regenerate complex structures has not yet been determined.…”
Section: Chemical Ablation Of β Cellsmentioning
confidence: 99%
“…By constitutive or conditional overexpressing targeted genes, the roles of thrombospondin-4 and p16 INK4a were investigated in spinal cord and limb regeneration 12 , 13 . However, transgenesis-based conditional gene overexpression requires the generation of transgenic animals, which can be time-consuming and is limited by the lack of well-characterized tissue-specific promoters 14 , 15 . In terms of knockout, it has been reported that introducing TALEN or CRISPR/Cas9 into fertilized eggs could efficiently lead to constitutive knockout/knockdown of targeted genes in axolotls 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%